Ciliotherapy Treatments to Enhance Biochemically- and Biophysically-Induced Mesenchymal Stem Cell Osteogenesis: A Comparison Study - Hoey, David (My University, 2019)
New approaches to treat osteoporosis have focused on promoting bone formation through the targeting of osteoblasts and their progenitors, mesenchymal stem cells (MSCs). The primary cilium is a singular cellular extension known to play an important role in biochemical and biophysical osteogenic induction of MSCs. Defects in ciliary structure have been associated with a plethora of diseases. Therefore targeting the cilium therapeutically (ciliotherapies) has emerged as a potential new treatment modality. Therefore, this study performed a comparison analysis on known ciliotherapies and their potential effects in mediating MSC osteogenic differentiation. Methods: MSCs were treated with forskolin, lithium chloride (LiCl) or fenoldopam to investigate the effect on ciliogenesis and cilia-associated signalling. Moreover, both early and long term biochemical and biophysical (fluid shear) induced osteogenic differentiation was examined in terms of osteogenic gene expression and bone matrix deposition following each treatment. Results: LiCl and fenoldopam were found to enhance MSC ciliogenesis to a similar degree. LiCl significantly altered hedgehog (HH) and Wnt signalling which was associated with inhibited osteogenic gene expression, while fenoldopam demonstrated enhanced early osteogenesis. Long term treatment with both ciliotherapies did not enhance osteogenesis, however LiCl had detrimental effects on cell viability. Intriguingly both ciliotherapies enhanced MSC mechanosensitivity as demonstrated by augmented osteogenic gene expression in response to fluid shear, which over longer durations resulted in enhanced matrix deposition per cell. Conclusions: Therefore, ciliotherapies can be utilised to enhance MSC ciliogenesis resulting in enhanced mechanosensitivity, however, only fenoldopam is a viable ciliotherapeutic option to enhance MSC osteogenesis.
PUBLISHED
Keywords: Bone; Oscillatory fluid shear; Primary Cilium; Mechanobiology; Hedgehog; Wnt